2009
DOI: 10.2337/db09-0693
|View full text |Cite
|
Sign up to set email alerts
|

A1C Variability Predicts Incident Cardiovascular Events, Microalbuminuria, and Overt Diabetic Nephropathy in Patients With Type 1 Diabetes

Abstract: OBJECTIVERecent data from the Diabetes Control and Complications Trial (DCCT) indicated that A1C variability is associated with the risk of diabetes microvascular complications. However, these results might have been influenced by the interventional study design. Therefore, we investigated the longitudinal associations between A1C variability and diabetes complications in patients with type 1 diabetes in the observational Finnish Diabetic Nephropathy (FinnDiane) Study.RESEARCH DESIGN AND METHODSA total of 2,10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
227
4
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 204 publications
(257 citation statements)
references
References 40 publications
18
227
4
6
Order By: Relevance
“…Twenty studies in 87,641 participants met the inclusion criteria. Ten studies included participants from Europe (10,11,14,(16)(17)(18)(19)26,29,35,36), eight from Asia (12,13,15,18,20,24,27,28), four from North America (6,18,23, 25), and one from Australasia (18). The number of participants in each study ranged from 234 to 35,891.…”
Section: Data Synthesis and Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…Twenty studies in 87,641 participants met the inclusion criteria. Ten studies included participants from Europe (10,11,14,(16)(17)(18)(19)26,29,35,36), eight from Asia (12,13,15,18,20,24,27,28), four from North America (6,18,23, 25), and one from Australasia (18). The number of participants in each study ranged from 234 to 35,891.…”
Section: Data Synthesis and Analysismentioning
confidence: 99%
“…Seven studies included 44,021 participants with type 1 diabetes (6,10,11,14,25,29,35). These comprised three retrospective cohort studies (11,14,25), two prospective cohort studies (10,29), one post hoc analysis of a randomized controlled trial (6), and one cross-sectional study (35).…”
Section: Type 1 Diabetesmentioning
confidence: 99%
See 2 more Smart Citations
“…15 Muggeo M et al in the Verona Diabetes study found long-term instability of fasting plasma glucose an independent cardiovascular risk factor in type 2 diabetics. 16 In our study 25 out of 29 (86 .2%) patients with Hba1c > 9 had positive treadmill test.…”
Section: Glycaemic Control and Silent Myocardial Ischemiamentioning
confidence: 99%